Reducing Poverty by Closing South Asia's Infrastructure Gap - Andrés, Luis (World Bank, Washington, DC, 2014)
Despite recent rapid growth and poverty reduction, the South Asia Region (SAR) continues to suffer from a combination of insufficient economic growth, slow urbanization, and huge infrastructure gaps that together could jeopardize future progress. It is also home to the largest pool of individuals living under the poverty line of any region, coupled with some of the fastest demographic growth rates of any region. Between 1990 and 2010, the number of people living on less than US$1.25 a day in South Asia decreased by only 18 percent, while the population grew by 42 percent. If South Asia hopes to meet its development goals and not risk slowing down, or even halting, growth and poverty alleviation, it is essential to make closing its huge infrastructure gap a priority. But the challenges on this front are monumental. Many people living in SAR remain unconnected to a reliable electrical grid, a safe water supply, sanitary sewerage disposal, and sound roads and transportation networks. This region requires significant infrastructure investment (roads, rails, power, water supply, sanitation, and telecommunications) not only to ensure basic service delivery and enhance the quality of life of its growing population, but also to avoid a possible binding constraint on economic growth owing to the substantial infrastructure gap.